2018
DOI: 10.1016/j.expneurol.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Subacute intranasal administration of tissue plasminogen activator improves stroke recovery by inducing axonal remodeling in mice

Abstract: In addition to thrombolysis, tissue plasminogen activator (tPA) can evoke neurorestorative processes. We therefore investigated the therapeutic effect of subacute intranasal administration of tPA post stroke on neurological recovery and on corticospinal innervation in mice. A transgenic mouse line, in which the pyramidal neurons and corticospinal tract (CST) axons are specifically labeled by yellow fluorescent protein (YFP) was employed. Adult CST-YFP mice were subjected to right unilateral middle cerebral art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Thus, the RFP labeling in the pyramidal neurons represents that these neurons physically and functionally connect to the peripheral tissue where the PRV tracer was injected. Consistent with our previous data, 6,14 RFP labeling was found in the layer V pyramidal neurons of both rostral and caudal forelimb motor areas, primarily in the ipsilesional cortex (Figure 6(a) to (c)), while scattered RFP-positive neurons were detected in the contralesional hemisphere (e–g) in stroke mice treated with saline (a and e), AAV-RFP (b and f), or AAV-tPA (c and g). The data showed that AAV-tPA treatment significantly increased the number of RFP-positive neurons in both ipsilesional (d, p < 0.01 vs. saline, p < 0.001 vs. AAV-RFP) and contralesional (h, p < 0.05 vs. saline, p < 0.01 vs. AAV-RFP) cortices.…”
Section: Resultssupporting
confidence: 93%
“…Thus, the RFP labeling in the pyramidal neurons represents that these neurons physically and functionally connect to the peripheral tissue where the PRV tracer was injected. Consistent with our previous data, 6,14 RFP labeling was found in the layer V pyramidal neurons of both rostral and caudal forelimb motor areas, primarily in the ipsilesional cortex (Figure 6(a) to (c)), while scattered RFP-positive neurons were detected in the contralesional hemisphere (e–g) in stroke mice treated with saline (a and e), AAV-RFP (b and f), or AAV-tPA (c and g). The data showed that AAV-tPA treatment significantly increased the number of RFP-positive neurons in both ipsilesional (d, p < 0.01 vs. saline, p < 0.001 vs. AAV-RFP) and contralesional (h, p < 0.05 vs. saline, p < 0.01 vs. AAV-RFP) cortices.…”
Section: Resultssupporting
confidence: 93%
“…In recent years, the long-term influence of tPA on CNS repair and plasticity after injury has begun to be elucidated. For example, tPA stimulates axonal sprouting at chronic stages after ischemic stroke (14), traumatic brain injury (15), and spinal cord injury (16,17), and these salutary effects correlate with improvements in neurological functions. However, whether tPA plays an indispensable role in poststroke functional recovery and the underlying mechanisms warrant further investigation.…”
Section: Significancementioning
confidence: 99%
“…Several clinical studies reported that fiber tract integrity was significantly related to motor impairment in patients with stroke [5,6]. Moreover, a significant body of evidence supports the importance of axonal reorganization in recovery after stroke [7][8][9][10][11]. The interplay between growth factors and microvascular cells prompts axonal sprouting and facilitates functional recovery [12].…”
Section: Introductionmentioning
confidence: 99%